Second Opinions and Price Competition Inefficiency in the Market for Expert Advice - Wolfgang Pesendorfer; Asher Wolinsky (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1998)
We analyze a market where the consumer must rely on expers to identify the correct type of service. Medical services, repair services and various types of consulting and advisory services belong to this broad category. Our focus is on situations where the diagnosis of the consumer's needs is costly and the expert's effort is unobservable. We develop a model where experts offer competing contracts and consumers may gather multiple opinions. In various contractual settings, we explore the incentives that a competitive sampling of prices and opinions provides for experts to exert effort. We find that there is a tension between price competition and quality of the advise provided in equilibrium. Under all the contracting scenarios considered, the equilibrium fails to realize the second best welfare optimum. In some of the cases, no gains from trade are realized. On the other hand, limiting price competition via price control increases total welfare.
Keywords: 330